Giant Magnetic Anisotropy in the Atomically Thin van der Waals Antiferromagnet FePS3. (8th December 2022) - Lee, Youjin; Son, Suhan; Kim, Chaebin; Kang, Soonmin; Shen, Junying; Kenzelmann, Michel; Delley, Bernard; Savchenko, Tatiana; Parchenko, Sergii; Na, Woongki; Choi, Ki‐Young; Kim, Wondong; et al.
Abstract: Van der Waals (vdW) magnets are an ideal platform for tailoring 2D magnetism with immense potential for spintronics applications and are intensively investigated. However, little is known about the microscopic origin of magnetic order in these antiferromagnetic systems. X‐ray photoemission electron microscopy is used to address the electronic and magnetic properties of the vdW antiferromagnet FePS3 down to the monolayer. The experiments reveal a giant out‐of‐plane magnetic anisotropy of 22 meV per Fe ion, accompanied by unquenched magnetic orbital moments. Moreover, the calculations suggest that the Ising magnetism in FePS3 is a visible manifestation of spin–orbit entanglement of the Fe 3 d electron system. Abstract : 2D van der Waals antiferromagnets are difficult to study using standard experimental techniques because of the net zero moments. Using the X‐ray photoemission electron microscopy technique with nanometer spatial resolution, antiferromagnetic signals are measured as a function of thickness, and observing the antiferromagnetic ground state of monolayer FePS3 as shown in the image is successful.